CAR, NPL, BOPO, and LDR on Profit Growth of BPR Riau Province Period 2015-2019 - Estu, Ahmad Zulkarnain; Rahayu, Sri; Irman, Mimelientesa; Anton; Eddy, Pujiono (Interconnection: An Economic Perspective Horizon, 2023)
The objective of this study is to analyze of capital adequacy ratio, non-performing loan ratio, operating expense to operating income, and loan deposit ratio to profit growth in rural banks in Riau Province for the 2015-2019 financial period. The sampling technique used was the purposive sampling method. The number of samples used in this study was 34 BPRs registered in Riau Province for the financial period 2015-2019. The analysis method used in this research is multiple regression analysis. The results showed that: partially CAR has a positive and insignificant effect on profit growth, partially NPL has a negative and insignificant effect on profit growth, partially BOPO has a negative and insignificant effect on profit growth, and partially LDR has a negative and significant effect on profit growth.